Comparative Physicochemical and Biological Properties of Two Strains of Kilham Rat Virus, a Non-defective Parvovirus - Mitra, S.; Snyder, C. E.; Bates, R. C.; Banerjee, P. T. (Journal of General Virology, 1982)
SUMMARY Two antigenically indistinguishable strains, 171 and 308, of Kilham rat virus (KRV) have distinct host ranges and contain capsid proteins of identical size, but with different isoelectric points. The single-stranded DNA genomes of the viruses are also the same size but appear to have different secondary and tertiary structures. The genomes of the two strains have nearly identical cleavage maps for 11 restriction endonucleases, except for differences in five restriction sites in the region bracketed by 0.63 to 0.90 map units (from the 3' ends of the virus strands). However, there is a lack of extended heterology in the nucleotide sequence of the two virus genomes, as judged by electron microscopic analysis of the heteroduplex of the two virus DNAs. This suggests that very subtle differences in the sequences of the genome, and possibly of the capsid proteins, may play a role in the host specificity without affecting the antigenic similarity of KRV strains.
Keywords: restriction endonuclease mapping